Case study : Casa Ermelinda Freitas : successful international strategies - Dias, Sebastião Manuel de Almeida (2016)
This dissertation aims to understand how Casa Ermelinda de Freitas, a successful Portuguese wine company, has been able to internationalize its business, maintaining a sustained competitive advantage in foreign markets, as well as the impact of it on the firm’s performance. The focus is to identify the entry strategies of the firm, the resources and capabilities needed to sustain a competitive advantage elsewhere and finally how did this strategies impact the company’s margins and performance. Globalization has opened the doors for firms to internationalize their products and business strategies. When a particular firm is concerned about its growth opportunities, the international markets become an important target, because of a natural opportunity to increase the volume of sales, as well as to reduce the overall business risk through diversification. Therefore, it is crucial to understand what strategies are more likely to help overcome the barriers of international markets, leading the business to another level. The wine industry has been suffering the effects of globalization for a long time. Many firms start the internationalization process, searching for a better performance. The new markets bring the possibility to increase volume and there is a non-confirmed prejudice that wine companies are also able to increase margins and thus improving performance when internationalized.